When Hollywood had a king the reign of Lew Wasserman, who leveraged talent into power and influence - Bruck, Connie (Random House, 2003)
A history of the Music Corporation of America traces the entertainment giant from its founding in 1924, through its rise to become the most powerful force in the film world under the visionary leadership of Lew Wasserman.